Observing the user experience : a practitioner's guide to user research - Kuniavsky, Mike (Morgan Kaufmann series in interactive technologies., 2003)
The gap between who designers and developers imagine their users are, and who those users really are can be the biggest problem with product development. Observing the User Experience will help you bridge that gap to understand what your users want and need from your product, and whether they'll be able to use what you've created. Filled with real-world experience and a wealth of practical information, this book presents a complete toolbox of techniques to help designers and developers see through the eyes of their users. It provides in-depth coverage of 13 user experience research techniques.